Distance Dependent Surface Enhanced Raman and Fluorescence by Supported 2D Assembly of Plasmonic Metal Nanoparticles - Ahamad, Nur; Al-Amin, Md.; Ianoul, A. (Asian Journal of Chemistry, 2013)
Metal nanoparticles polyelectrolytes nanocomposite substrates consisted of variable number of poly(sodium-4-styrenesulfonate)/poly(diallyldimethylammonium chloride) bilayers deposited on supported 2D assembly of silver nanoparticles were fabricated using layer by layer deposition technique. Rhodamine 6G and poly(fluorescein isothiocyanate allylamine hydrochloride) were subsequently deposited onto these substrates to investigate distance dependent surface enhance Raman scattering and fluorescence of these substrates. The as prepared substrates exhibited surface enhanced Raman scattering and fluorescence activities. Even though precise distance control between rhodamine 6G and nanoparticles was rather impossible due to the fluorophore diffusion, a 14 fold enhancement of the rhodamine 6G fluorescence signal was detected. In addition, surface enhanced Raman scattering enhancement of rhodamine 6G containing substrates was noticed at a separation distance corresponding one bilayer. On the contrary for poly(fluorescein isothiocyanate allylamine hydrochloride), a modest 2-fold enhancement of fluorescence was observed for a separation distance corresponds to 30 bilayers.